IMF interventions and financial market reactions: evidence from currency, equity, and interest rate markets in emerging and developed economies - Díaz-Chapoñan, Walther Fernando; Alexiou, Constantinos; Vogiazas, Sofoklis (MDPI, 2026)
This paper examines how International Monetary Fund (IMF) lending affects financial markets across emerging and developed economies from 2002 to 2023 using an event study approach. Our findings indicate that IMF loans are typically granted during periods of global financial distress. While aggregate effects on debt, currency, and equity markets appear limited, a more detailed analysis reveals significant shifts in currency and stock markets around loan announcements. Notably, markets often react up to seven days before an official IMF announcement, with the strongest effects seen in the interest rate markets of emerging economies. These findings highlight the importance of tailoring IMF programs to account for market heterogeneity and structural differences between developed and emerging economies.
This article belongs to the Section Applied Economics and Finance
Keywords: 38 Economics; 3502 Banking, Finance and Investment; 3801 Applied Economics; 35 Commerce, management, tourism and services; IMF programs; event study; financial markets; capital markets